Emprendimiento de consultoría en gestión del cambio - Escalante Castañeda, Lucia Marie (2019)
Adapting to changes turns out to be a growing challenge for enterprises that if left unchanged, run the risk to lose validity or simply disappear. Even though, in this context, technology is a need, and in many cases, is the foundation to implement entrepreneurial strategies, the best transformational strategy, as well as the most important investment, would be useless if we do not have the right human factor, with the capabilities, the experience and the motivation needed to promote technological and cultural changes. Statistics show that very few of the transformation projects fail due to technological flaws, or defects in the processes. However, those factors related to the human component, such as lack of motivation, lack of commitment or collaboration, as well as communication barriers and absence of leadership, among others, can predict to a large extent the failure of a transformation project. For this reason, in this consulting proposal, we will focus on a critical variable for any transformation process: people, and we will provide with a methodology of Change Management aimed to go with the cultural and technological transformation projects.